(Reseña) Fray Eugenio Torres Torres (coord.), "Los dominicos insurgentes y realistas, de México al Río de la Plata" - Vargas Cariola, Juan Eduardo (Historia, 2012)
Las "Reseñas bibliográficas" no contemplan resumen.